2017
DOI: 10.21101/cejph.a4464
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Characteristics, Health Risk Factors and Alcohol Consumption among the Homeless in North-Eastern Part of Poland

Abstract: Our results indicate that the design of the social welfare system for homeless people should always take into account issues related to alcohol dependence, and each homeless person should be evaluated for possible alcohol dependence. Institutionalised material support provided to homeless individuals should be organised in such a way as to minimise the risk of promoting alcohol and nicotine dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 19 publications
3
7
0
2
Order By: Relevance
“…It is a serious problem especially during late autumn and in winter when the temperature is below 0°C, which poses a threat to their health and lives. Romaszko et al point out that the problem is growing with the number of people drinking alcohol (78.5% in Poland), making them sensitive to hypothermia (7). Unfortunately, it is often caused by addiction maintained due to the fear of the effects of withdrawal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a serious problem especially during late autumn and in winter when the temperature is below 0°C, which poses a threat to their health and lives. Romaszko et al point out that the problem is growing with the number of people drinking alcohol (78.5% in Poland), making them sensitive to hypothermia (7). Unfortunately, it is often caused by addiction maintained due to the fear of the effects of withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Romaszko i wsp. wskazują, iż problem z otrzymaniem noclegu rośnie wraz z liczbą osób pijących alkohol (78,5% w Polsce), co czyni je wrażliwymi na hipotermię (7). Niestety, często jest to spowodowane uzależnieniem utrzymywanym przez strach przed skutkami wycofania.…”
Section: Discussionunclassified
“…Although American and West European authors indicate evident over-representation of racial and ethnic minorities among the homeless, this is not observed in Central European countries, slightly less attractive as the target for emigration [6]. Moreover, the homeless described by American and West European authors are generally slightly younger than those reported by researchers from Central and Eastern Europe [7, 8]. This seems to be related to the etiology of homelessness.…”
Section: Introductionmentioning
confidence: 99%
“…This correlation is also noticeable in Poland, where the homeless subpopulation is evidently older and definitely more often dependent on alcohol than drugs. In a study conducted in Olsztyn, Poland, Romaszko et al estimated the percentage of the homeless addicted to alcohol at more than 78%, and the average age of the studied group at 55 years of age [8]. These values suggest that statistically rates of early mortality should be rather smaller than larger as compared to data obtained in the West.…”
Section: Introductionmentioning
confidence: 99%
“…In the city of Olsztyn, Poland, for example, a census of the street population was carried out in 2013, which showed that the majority of the individuals (93%) were male, had a mean age of 54 years, were dependent alcohol (79%), smoker (85%), low education, and almost one-third (33%) stated that they occasionally starved, and the main source of food was meals offered by social services (90%). 4 It is recognized internationally that public policies must take into account the social determinants of health, taking into account all the social factors that may be involved in the process of sickness of the individual and of the population. In this context, the concept of health is understood beyond a biological perspective and one must consider the individual's experience in society and access to the socioeconomic and essential services networks, since the social context and individual life history and the community will influence this process.…”
mentioning
confidence: 99%